Arte/Educação na perspectiva da identidade negra: reflexões sobre educação antirracista - Portella, Gabriel Vieira (Universidade Federal de São Carlos, 2023)
The purpose of this work is to discuss the importance of anti-racist education as a part of Art/Education, serving as a catalyst for new cultural paradigms. This perspective is highlighted in the teaching of Art through the enactment of laws 10.639/2003 and 11.645/2008, which make it mandatory to include African and Afro-Brazilian history and culture in the school curriculum, with an emphasis on History, Art, and Literature subjects. The main research question is: "What is the significance of Art/Education in anti-racist education?" To address this question, the author of this study explored personal learning experiences in the field of Art, official legislations, and relevant bibliographical references on the topic. The results point to the urgency of combating racism in pedagogical practices, which often remain rigid and suppress black identity, leading to stigmatization. Several factors contribute to progress in this matter, with one of them being teacher artistic training. This perspective believes it is essential to promote the teaching of African and Afro-Brazilian arts in Basic Education and initial teacher training, in order to value black identity within our society and counter structural racism.
Art/Education from the perspective of black identity: reflections on anti-racist education
Keywords: Arte/Educação; Art/Education; Arte afro-brasileira; Afro-Brazilian Art; Identidade negra; Black identity; Educação antirracista; Anti-racist Education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO